2021
DOI: 10.3389/fmed.2021.595371
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Non-alcoholic Fatty Liver Disease. An Updated Mini Review

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a challenging disease caused by multiple factors, which may partly explain why it remains still orphan of an adequate therapeutic strategy. Herein we focus on the interplay between oxidative stress (OS) and the other causal pathogenetic factors. Different reactive oxygen species (ROS) generators contribute to NAFLD inflammatory and fibrotic progression, which is quite strictly linked to the lipotoxic liver injury from fatty acids and/or a wide variety of their biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 162 publications
(176 reference statements)
2
134
0
Order By: Relevance
“…Furthermore, a high intake of fat and carbohydrates can induce ER stress, and dysfunction of ER develops metabolically-driven NAFLD progress [ 73 , 74 ]. Although this study revealed that HCA had therapeutic effects by suppressing lipid accumulation and apoptosis in liver cells, other components may be effective to NAFLD since recent clinical trials suggest that protein oxidation/glycation and ER stress are involved in liver fibrosis in NAFLD [ 75 , 76 ]. Thus, further studies are needed to investigate additional anti-NAFLD effects and the underlying mechanism of the G. cambogia and its components.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a high intake of fat and carbohydrates can induce ER stress, and dysfunction of ER develops metabolically-driven NAFLD progress [ 73 , 74 ]. Although this study revealed that HCA had therapeutic effects by suppressing lipid accumulation and apoptosis in liver cells, other components may be effective to NAFLD since recent clinical trials suggest that protein oxidation/glycation and ER stress are involved in liver fibrosis in NAFLD [ 75 , 76 ]. Thus, further studies are needed to investigate additional anti-NAFLD effects and the underlying mechanism of the G. cambogia and its components.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, ROS causes damage to DNA, lipids, and proteins, forming oxidative damage products [ 51 ]. Following lipotoxic liver injury, ER stress and DNA damage promote further NAFLD inflammation and fibrotic progression [ 52 ].…”
Section: The Role Of Os and Inflammation In Nafldmentioning
confidence: 99%
“…Based on this, the plasma FGF21 concentration has even been suggested as a surrogate marker for fatty liver in humans [105,106]. It has been recognized that the development of a non-alcoholic fatty liver disease (NAFL D) in humans, which is frequently associated with obesity, is caused by multiple pathophysiological factors including inflammation, ER stress, oxidative stress and elevated plasma concentrations of NEFA [107]. These factors are considered to act as triggers for the induction of hepatic FGF21 expression [11,35].…”
Section: Role Of Fgf21 For Metabolic Diseases In Dairy Cowsmentioning
confidence: 99%